Colonoscopic polypectomy of juvenile polyps in children: Experience from a tertiary centre of Bangladesh - Salahuddin Mahmud; Mashud Parvez; Madhabi Baidya; Farhana Tasneem; Ahmed Rashidul Hasan; Tanzila Farhana; Md Jahangir Alam; Syed Shafi Ahmed (Gastroenterology & Endoscopy, 2024)
Aims: To assess the specifics of juvenile polyps and the value of polypectomy with complete colonoscopy in pediatric patients. Methods: I retrospectively reviewed the medical records of 81 children diagnosed with juvenile polyps from 2017 to 2021. Results: The patients' ages ranged from 1.5 to 18 years. Hematochezia was present in 100% of cases, in which 97.5% of the bleeding was painless. The most frequent was red or dark red hematochezia in 71.6% of cases, followed by red stool with blood dripping in 9 (11.1%) cases. The time interval between the first episode of hematochezia and the colonoscopy ranged from 1 to 47 months. Only 24.7% of polyps were diagnosed by digital rectal examination. Most of the Juvenile polyps were solitary (82.8%) and located in the rectosigmoid part of the colon. The size of the polyps varied from 0.3 to 4 ​cm. Early post-polypectomy bleeding occurred in two cases, while late post-polypectomy bleeding occurred in only one case. Conclusions: Although solitary juvenile polyps in the rectosigmoid colon are more common, some patients had multiple and some had proximal polyps. Therefore, a colonoscopy of the entire colon with therapeutic polypectomy is important for improved outcomes when evaluating painless, intermittent hematochezia in children.